PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS APLIKASI FISIKA GERAK LURUS TERHADAP PEMAHAMAN KONSEP FISIKA SMA - Sijabat, Apriani; Girsang, Astri Ananta; Lumbangaol, Sudirman TP; Siahaan, Fine Eirene (UNIB Press, 2025)
The low conceptual understanding of straight motion among high school students, often caused by conventional and less interactive teaching methods, served as the foundation of this study. This research to examine the influence of using a straight motion physics learning application on students’ conceptual comprehension. A quantitative approach was employed through a quasi-experimental method using the Nonequivalent Control Group Design. The experimental group engaged with an interactive Android-based application, while the control group received instruction through traditional methods. The study addresses the gap in the lack of empirically tested game-based educational media in high school physics learning. Analysis revealed a statistically significant difference in posttest results (p = 0.039), with the experimental group scoring higher on average than the control group. The findings suggest that interactive application-based media exerts a positive influence on students’ learning motivation, which in turn enhances their conceptual understanding, particularly in the study of straight motion.